HEMAT ENERGI DAN BAHAYA LISTRIK DI POSYANDU LANCANG KUNING RT 04 RW 15 KECAMATAN TAMPAN - Monice; Perinov (Universitas Lancang Kuning, 2019)
Electricity is one of the energy sources of human life today, almost everyone, every day for24 hours uses electricity as an energy source to help and facilitate daily activities. Actually, thepublic understands to always apply electricity-saving life in carrying out daily atifities, but so farthe public's understanding of electricity-saving activities is still limited to their goal of savingelectricity bill costs. and child. With a background of different parents and the age of childrenbetween 0-5 years is a period of brain development which is in a sensitive period where children inparticular are easy to accept and absorb various kinds of information and stimuli from theenvironment. This phase is the best time to teach and familiarize children to save electricity byinstilling good understanding and awareness, which they will continue to bring to their growth andlife in the future. The method of implementing science and technology activities for the communityincludes several methods, namely providing material about energy savings with socialization toparents and the dangers that will be caused. And parents will give this approach to their childrenin the home environment